Il Faust di Goethe come tragedia filosofica - D’Angelo, Paolo (Bollettino Filosofico, 2017)
Many philosophers, both in Nineteenth Century and in Twentieth Century have discussed Goethe’s masterpiece Faust. But not all their interpretations are philosophical interpretations of the Drama. Christian Hermann Weiße and Friedrich Theodor Vischer, as well as Heinrich Rickert and Benedetto Croce red the Tragedy as a literary work. In reading the Poem they acted not qua philosophers, but qua literary critics. The present essay discusses a another type of reading of the Drama, i.e. the interpretations which regard the Text as a philosophical Work and not only as a literary product. Apparently, Hegel was the first who spoke of Goethe’s Faust in terms of die absolute philosophische Tragődie, the absolute philosophical Tragedy. Indeed, it was probably Hegel’s student, H. Hotho, who first used this definition. This circumstance did not prevent Ernst Bloch from regarding Faust as a literary transposition of Hegel’s dialectic. George Santayana, on the contrary, has regarded Goethe’s Drama as the illustration of the philosophy of Romanticism, while recently and quite surprisingly Gernot Bőhme has seen in the Drama an ironic confutation of the smoothed human pretense of annihilating Nature through Technique.